A window into the village core: cultivation, clearance and construction in medieval Dersingham, Norfolk - White, Joshua C; Dobson, David; Brown, David W (Medieval Settlement Research, 2025)
This paper reports on an excavation carried out within a post-medieval walled garden in Dersingham, Norfolk. The investigation revealed archaeological features, deposits and finds which shed light on the development of part of the settlement’s historical core across the mid-eleventh to mid-sixteenth centuries. This paper finds that activity was limited before the thirteenth to fourteenth centuries, when the establishment or consolidation of the local church and manor probably gave rise to greater nucleation in the settlement. Remodelling work between the fourteenth and mid-fifteenth centuries, probably associated with the church, produced a large amount of debris, including masonry, roof tiles and a significant assemblage of painted window glass. A significant clearance and levelling event occurred in the second half of the fifteenth century, followed by the construction of a brick structure, which lasted until the surviving structures were built in the mid-sixteenth century.